RELATIONSHIP OF AGE, GENDER, LENGTH OF WORK AND APPLICATION OF OHS MANAGEMENT SYSYEM DURING COVID-19 PANDEMIC TO STRESS EVENTS IN HEALTH WORKERS - Resy Asmalia; Putri Zalika Laila; Ratika Febrianti; Ulfah Haniyah (Majalah Kedokteran Sriwijaya, 2022)
Health workers are at the forefront of responding to the COVID-19 emergency, which is at higher risk from various groups of workers. During the COVID-19 pandemic, workers may experience increased stress stemming from uncertain work situations, as well as increased stress for emergency response workers due to the application of strict K3 measures in preventing transmission, for example by using heavy PPE, applying physical isolation and etc. The purpose of this study was to determine the relationship between age, gender and length of work of health workers on stress with the application of an OHS management system during the COVID-19 pandemic. This research is analytic observational with cross sectional design. The study was conducted at the Kayu Agung Hospital. The population of this study were health workers at the Kayu Agung Hospital. The sample of this research is health workers, namely doctors and nurses with a total sample of 97 respondents. The data collection instrument used a questionnaire. Analysis of research data is univariate and bivariate using the chi square test. The results showed that there was no significant relationship (p>0.05) between age, gender, length of work on the incidence of stress during the COVID-19 pandemic and there was a significant relationship (p<0.05) between the implementation of the OHS management system and the incidence of stress, Odd value The ratio (OR) of 3.265 means that respondents who implement the OHS management system well are at risk of 3,265 times experiencing stress events compared to respondents who implement the OHS management system satisfactorily.The conclusion of this study is that only the application of the OHS management system has a significant relationship with the incidence of stress. It is hoped that it will increase the socialization of K3 and the application of the OHS management system, as well as manage stress with positive thinking patterns and apply a healthy lifestyle.